Statement from the Early Career Member Committee (ECMC) Chair and Co-chair and introduction of the new ECMC members - Ubags, Niki (2021)
The Early Career Member Committee (ECMC) of the European Respiratory Society (ERS) consists of a group of 14 ERS members below 40 years of age, who represent the interests of the Early Career Members (ECMs) from the assemblies. Each ECM representative has specific tasks within the ECMC, which have been presented in a previous issue of Breathe [1]. In 2020, Niki Ubags and Maxime Patout took up the position of Chair and Co-chair of the ECMC and two ECMs joined the Committee and became the ECM representatives for Assemblies 6 and 9. This article provides a statement from the ECMC Chair and Co-chair and introduces the two new members of the ECMC.